Evaluating the impact of season and breeding area on blood parameters in Pramenka sheep exposed to thermal stress conditions (VETERINARIA, 2025)
This study aimed to investigate seasonal variations in blood parameters of two Pramenka sheep strains, Dubska and Hercegovacka, across and within four areas in Bosnia and Herzegovina, under thermal stress conditions. It included 48 sheep from Vlasic and Kupres (breeding areas of the Dubska strain), and Nevesinje and Podvelezje (breeding areas of the Hercegovacka strain). The investigation was conducted across both summer and winter seasons, encompassing a total of eight herds (two per area). Hematological parameters included erythrocyte, leukocyte, and platelet counts, mean platelet volume (MPV), the total count of granulocytic and agranulocytic leukocytes, hemoglobin concentration (Hb), red blood cell distribution width (RDW) and erythrocyte parameters (MCV, MCH and MCHC). Biochemical analyses covered total bilirubin (TB), total cholesterol (TC), glucose (GLU), urea (UREA), creatinine (CRE), creatine kinase (CK), non-esterified fatty acids (NEFA), beta-hydroxybutyrate (BHB), proteins, liver enzymes and electrolytes. Results revealed significantly higher values of red blood cell parameters (Hb, MCH, MCHC) during the summer period in the area of Nevesinje (P
Keywords: blood parameters; sheep; Pramenka; thermal stress; season